Prevalence of substandard and falsified artemisinin-based combination antimalarial medicines on Bioko Island, Equatorial Guinea - Kaur, Harparkash (2017)
Introduction Poor-quality artemisinin-containingantimalarials (ACAs), including falsified and substandardformulations, pose serious health concerns in malariaendemic countries. They can harm patients, contributeto the rise in drug resistance and increase the public?smistrust of health systems. Systematic assessment of drugquality is needed to gain knowledge on the prevalence ofthe problem, to provide Ministries of Health with evidenceon which local regulators can take action.Methods We used three sampling approaches topurchase 677 ACAs from 278 outlets on Bioko Island,Equatorial Guinea as follows: convenience surveyusing mystery client (n=16 outlets, 31 samples), fullisland-wide survey using mystery client (n=174 outlets,368 samples) and randomised survey using an overtsampling approach (n=88 outlets, 278 samples). Thestated active pharmaceutical ingredients (SAPIs) wereassessed using high-performance liquid chromatographyand confirmed by mass spectrometry at threeindependent laboratories.Results Content analysis showed 91.0% of ACAs wereof acceptable quality, 1.6% were substandard and7.4% falsified. No degraded medicines were detected.The prevalence of medicines without the SAPIs washigher for ACAs purchased in the convenience surveycompared with the estimates obtained using the fullisland-wide survey-mystery client and randomised-overtsampling approaches. Comparable results were obtainedfor full island survey-mystery client and randomisedovert. However, the availability of purchased artesunatemonotherapies differed substantially according to thesampling approach used (convenience, 45.2%; fullisland-wide survey-mystery client, 32.6%; random-overtsampling approach, 21.9%). Of concern is that 37.1%(n=62) of these were falsified.Conclusion Falsified ACAs were found on Bioko Island,with the prevalence ranging between 6.1% and 16.1%,depending on the sampling method used. These findingsunderscore the vital need for national authorities to trackthe scale of ineffective medicines that jeopardise treatmentof life-threatening diseases and value of a representativesampling approach to obtain/measure the true prevalenceof poor-quality medicines.